Phosphatase and tensin homolog deleted on chromosome 10 degradation induced by NEDD4 promotes acquired erlotinib resistance in non–small-cell lung cancer - Huake Sun; Huiwen Ma; Jianmin Wang; Liqin Xia; Guangkuo Zhu; Zhoufei Wang; Jianguo Sun; Zhengtang Chen (Tumor Biology, 2017)
Acquired resistance to epidermal growth factor receptor-tyrosine kinase inhibitors, such as gefitinib and erlotinib, is a critical issue in the treatment of patients with epidermal growth factor receptor mutant–positive non–small-cell lung cancer. Recent evidence suggests that downregulation of gene of phosphatase and tensin homolog deleted on chromosome 10 plays an important role in acquired resistance to epidermal growth factor receptor-tyrosine kinase inhibitors in various types of cancers, including lung cancer. It was reported that the E3 ubiquitin ligase neural precursor cell expressed developmentally downregulated gene (NEDD4) (also known as NEDD4-1) negatively regulated phosphatase and tensin homolog deleted on chromosome 10 protein levels through poly-ubiquitination and proteolysis in carcinomas of the prostate, lung, and bladder. Whether this process plays a role in epidermal growth factor receptor-tyrosine kinase inhibitors resistance in non–small-cell lung cancer has not been studied extensively. In view of this, we investigated the involvement of NEDD4 and phosphatase and tensin homolog deleted on chromosome 10 in acquired erlotinib resistance with tyrosine kinase inhibitor–sensitive (HCC827) or tyrosine kinase inhibitor–resistant (Erlotinib-resistant HCC827/ER cells which harbored exon 19 deletion. Overexpression of NEDD4 in HCC827/ER cells was detected, and the reverse correlation between NEDD4 and phosphatase and tensin homolog deleted on chromosome 10 expression in these cells was also revealed. In HCC827/ER cells with knockdown of NEDD4 , phosphatase and tensin homolog deleted on chromosome 10 and p-Akt expressions were decreased; the sensitivity of HCC827/ER cells to erlotinib was partially restored. Similar results were also observed in vivo. In H1650/ER cells harboring both exon 19 and phosphatase and tensin homolog deleted on chromosome 10 deletion, expression of p-Akt and sensitivity to erlotinib were not affected by simple knockdown of NEDD4 but affected after transfection of phosphatase and tensin homolog deleted on chromosome 10 into H1650/ER cells. Our results demonstrate that NEDD4 may promote the acquired resistance of non–small-cell lung cancer cells to erlotinib by decreasing phosphatase and tensin homolog deleted on chromosome 10 protein expression. Targeted decrease in NEDD4 expression may be a potential therapeutic strategy for tyrosine kinase inhibitor–resistant non–small-cell lung cancer.